2015
DOI: 10.1109/tnsre.2014.2377692
|View full text |Cite
|
Sign up to set email alerts
|

A Nonlinear Model for Mouse Pointing Task Movement Time Analysis Based on Both System and Human Effects

Abstract: This paper provides a detailed model for analyzing movement time performance during rapid goal-directed point- and-click motions with a computer mouse. Twelve typically developed individuals and eleven youths with cerebral palsy conducted point and click computer tasks from which the model was developed. The proposed model is nonlinear and based on both system (target width and movement amplitude) and human effects (erroneous clicks, number of submovements, number of slip-offs, curvature index, and average spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Recent advances in this direction are mainly focused on their extension, e.g. a model for analyzing rapid point-and-click motions taking into account human effects has been recently proposed in [12].…”
Section: Modeling Pointing Motionsmentioning
confidence: 99%
“…Recent advances in this direction are mainly focused on their extension, e.g. a model for analyzing rapid point-and-click motions taking into account human effects has been recently proposed in [12].…”
Section: Modeling Pointing Motionsmentioning
confidence: 99%
“…The first study showed that for individuals with CP, it is more important to focus on the development of user interfaces and algorithms to increase speed because they already appear to have sophisticated accuracy [13]. The second study examined both system (width and amplitude) and human effects (errors, slips off the target, etc) that contribute to the speed and accuracy of cursor movement of youths with CP and determined that the most significant human effect is the curvature index [14]. The curvature index is the ratio of the total distance traveled to the straight-line distance between the start and end points.…”
Section: The Proposed Algorithmmentioning
confidence: 99%
“…Despite the above approach, the issue of how to model the less-affected arm persists. Several statistical models have captured quantifiable reaching characteristics [ 24 26 ]; however, to the best of our knowledge, there is no appropriate model for evaluating the normal RM of stroke. Fitts’ law, which is the most well-known reaching model [ 24 ], has been applied to quantify the reaching performance of stroke survivors.…”
Section: Introductionmentioning
confidence: 99%